Exploration and research on the product design method of YangJiaBu new year woodcut prints from the perspective of social innovation / Zhang Yuzhu, S'harin Mokhtar and Natrina Mariane P. Toyong - Zhang, Yuzhu; Mokhtar, S'harin; P. Toyong, Natrina Mariane (Faculty of Art and Design, 2024)
This theme comes from YangJiaBu new year woodcut prints, one of China's intangible cultural heritages. Currently, cultural innovation is attracting attention in the development of the global cultural industry and also occupies an important position in China's cultural strategy, bringing new opportunities for the revival of traditional culture. However, this folk culture is facing complex status and development problems, and its development needs to be actively promoted by all forces. This study aims to better promote the cultural innovation of YangJiaBu new year woodcut prints and explore the design method and process of integrating it into daily use innovation. The research adopts fieldwork, interviews, literature research and case study methods, and thematic analyses. In conclusion, these studies will help to identify key themes from current cultural developments, sort out design methods and processes, and provide insights that will make the daily-use innovation of YangJiaBu new year woodcut prints more product-identifiable and innovative, add sources of inspiration for modern design and social innovation, and continue to maintain an important position and influence in the future for the inheritance and development of China's traditional culture.